Application of Thought Stopping (TS)/Stopping Negative Thoughts in Families in Providing Support for Family Members with Hypertension in Harjosari Village, Sukajadi District, Pekanbaru City: Penerapan Thought Stopping (TS)/Menghentikan Pikiran Negatif Pada Keluarga Dalam Memberikan Dukungan Bagi Anggota Keluarga Dengan Hipertensi Di Kelurahan Harjosari Kecamatan Sukajadi Kota Pekanbaru - Usraleli, Usraleli; Forwaty, Erni; Oktaviani, Ira; Rusdi, Ibnu (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Hypertension (referred to as "the silent killer") is one of the non-communicable diseases that can be quite dangerous if left uncontrolled, even leading to death. The mortality rate is 427,218 deaths out of Indonesia's population of 268,369,114. Hypertension complications include myocardial infarction, left ventricular hypertrophy, heart failure, aneurysm, and chronic kidney disease (Jelaković, 2022). According to Athiyah et al. (2019), hypertension is currently on the rise and requires long-term treatment. Hypertension ranks third in the outpatient data of BPJS Health participants in 2018, with the highest number of sufferers in Indonesia (Pusparisa & Ridhoi, 2020). This Community Service Activity will be conducted at the PTM Posyandu in Harjosari Village, Sukajadi District, Pekanbaru City, because Harjosari Village has been a community development area under the Riau Health Polytechnic (Poltekkes Kemenkes Riau) since 2021 and will continue until 2024. In addition, the choice of Harjosari Village for this program is based on interviews with clients, revealing that 22 clients actively visit the Posyandu in RW 01 and RW 04. The Posyandu in RW 01 is located in the prosecutor's housing complex, while the Posyandu in RW 04 is located on Bunga Harum Street. Based on initial surveys at the site, it was found that there were 5 clients with hypertension who were not receiving adequate support from their families. The purpose of this community service program is to assess the application of Thought Stopping (TS) to help families provide better support to family members with hypertension. The program will run from February to October 2024 (8 months). The activity will focus on applying Thought Stopping (TS) techniques to stop negative thoughts. The target audience for this program consists of 25 individuals. The implementation of the Thought Stopping therapy will be conducted in three sessions: Session 1: Stopping negative thoughts after hearing an alarm sound. Session 2: Stopping negative thoughts after seeing the word “STOP”. Session 3: Stopping negative thoughts after whispering or saying something quietly to oneself. The techniques used will include describing, modeling, role-playing, providing feedback, and transferring knowledge. A required output for this program is a scientific article published in a nationally accredited community service journal (Sinta 4), and an additional output will be intellectual property rights (HaKI).